Minister of Finance Incorporated ownership and control of corporate Malaysia - Gomez, Edmund Terence; Padmanabhan, Thirshalar; Norfaryanti Kamaruddin; Bhalla, Sunil; Fikri Fisal (Palgrave Macmillan Strategic Information and Research Development Centre, 2011)
This is a study of Malaysia's new political economy, with a focus on ownership and control of the corporate sector. It offers a pioneering assessment of government-linked investment companies (GLICs), a type of state-owned institution that has long prevailed in the corporate sector but has not been analysed. Malaysia's history of government-business ties is unique, while the nature of the nexuses between the state and the corporate sector has undergone major transitions. Corporate power has shifted from the hands of foreign firms to the state to the ruling party, and well-connected businessmen, and back to the state. Corporate wealth is now heavily situated in the leading publicly-listed government-linked companies (GLCs), controlled through block shareholdings by a mere seven GLICs under the jurisdiction of the Minister of Finance. To indicate why these GLICs are important actors in Corporate Malaysia, this study provides a deep assessment of their ownership and control of Bursa Malaysia's top 100 publicly-listed enterprises.